Structural Design and Kinematics Simulation of Reconfigurable Modular Fixture Robot based on Automobile Sheet - Zhang Liwang; Ge Weimin; Wang Xiaofeng; Liu Zengchang (Jixie chuandong)
The fixture is important process equipment in the automobile body assembly,and the reusability of fixture has become the key factor to hinder the efficiency of automobile production efficiency and assembly restructuring. For the automotive components of the sheet with different curvature radius,a set of reconfigurable modular fixture is designed. The sheet with different curvature radius is clipped,and it is not necessary to reconstruct the system,this is widely used in industrial production design standards. A modular fixture is designed,and its kinematics analysis is carried out to verify its rationality and stability.